GHGs mitigation in diffuse sectors: Climate funding and biomass potential in Spain and climate funding. Success story (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The potential for reducing emissions of greenhouse gases in the so-called “diffuse sectors” in Spain, through mitigation actions based on energy efficiency measures and implementation of renewable energy is extraordinarily high. In order to promote the transformation of the Spanish production system into a low emissions of greenhouse gases model, several funding lines have been approved for these sectors. This article describes the role that biomass can play in the gradual decarbonization of the energy matrix, with initiatives such as the Climate Projects.